Lambert-Eaton Myasthenic Syndrome Secondary to Nivolumab and Ipilimumab in a Patient with Small-Cell Lung Cancer - Kavita Agrawal; Nirav Agrawal (Case Reports in Neurological Medicine)
We present a case of a 59-year-old male with a confirmed diagnosis of small-cell lung cancer (SCLC). He had progressive disease even after four cycles of cisplatin and etoposide chemotherapy and 21 cycles of radiation. He was therefore started on immunotherapy with nivolumab every 2 weeks and ipilimumab every 6 weeks. After 4 months of starting immunotherapy, he reported extreme fatigue, muscular weakness, and poor appetite. He was diagnosed with hypothyroidism, primary adrenal insufficiency, and Lambert-Eaton Myasthenic Syndrome (LEMS). LEMS can be both a paraneoplastic syndrome of SCLC and an adverse effect of immunotherapy. Currently, there is no diagnostic test available to determine if a case of LEMS is a paraneoplastic syndrome or immunotherapy-related adverse effect. In our patient, we felt that LEMS was an immunotherapy-related adverse effect rather being a paraneoplastic syndrome. Our determination was based on the time of onset of muscular weakness, presence of other immunotherapy-mediated adverse events, and the appearance of symptoms in spite of SCLC that had been stabilized on immunotherapy. Accordingly, immunotherapy was stopped and a brief tapering course of steroids was initiated. Our patient’s muscular weakness from LEMS responded well. His clinical improvement persisted even with radiologic progression of disease after cessation of immunotherapy.